Compacting SQL queries for saving resources in mobile ad hoc and sensor networks. (17th December 2009) - Artail, Hassan; Safa, Haidar; Idris, Anas
This paper presents an SQL query compaction scheme that makes accessing data in mobile ad hoc networks and in wireless sensor networks more efficient. The proposed scheme exploits the SQL syntax and generates a light-weight binary representation that significantly shrinks the size of the queries. Its performance was evaluated after being implemented using the Java 2 Micro Edition (J2ME) platform and deployed on a Sony Ericsson P800 mobile phone. The considered test queries were a representative sample applicable to the SQL syntax of the TinyDB sensor network database. Results show an achieved compaction ratio that is less than 1.6 bits per byte or equivalently greater than 80%, which greatly outperforms the Huffman coding algorithm.